Molecular approach to solids - Lazarev, A. N. (Adrian Nikolaevich) (Vibrational spectra and structure ;, 1998)
The current volume in the series Vibrational Spectra and Structure is a single topic volume on the vibrational spectra of molecules containing silicon in the solid state. Molecular Approaches to Solids has been treated by the workers in the Institute for Silicate Chemistry of the Russian Academy of Science in St. Petersburg for the past two decades. In the last 15 years, a number of publications have originated from the laboratory where quantum mechanical computations for suitably selected molecules have been utilized to explain the origins of some structure bonding interrelationships and silicates and to evaluate their force constants. Since most of the developments in this area have been published in the Russian literature they remain relatively inaccessible to the Western scientists. This volume is a compilation of many of these publications and summarizes the essential conclusions of these studies. Unfortunately, Professor Lazarev passed away after he had submitted the volume for publication.